Students’ occupational commitment: Relationship with the satisfaction of occupational choice, career aspirations and career adaptability - Jokštaitė, Kristina; Pociūtė, Birutė (Psichologija, 2014)
Student’s readiness to become successful in their future profession is one of the most important goals not only in the realization of academic aims, but also in making the commitment to their profession. At the moment a student enters the university, college, or vocational school, we assume that his or her commitment toward a career choice is essentially made. However, not all students can make an occupational commitment on the basis of a rational choice. Even if the occupational choice is successful and matches the student’s abilities, desires and market needs, this does not guarantee that after graduation a student will choose the career path related to the chosen occupation. The development of occupational commitment begins with occupational choice, and changes are based on individual experience related to occupational choice satisfaction, expectations for the future work, a student’s ability to collect information about oneself and possible career options and to overcome the obstacles of the chosen career path. The aim of this study was to investigate the relationship between vocational technical school, college and university students’ occupational commitment and occupational choice satisfaction, career aspirations, career adaptability. In the study, 356 students from vocational technical schools, colleges and universities took part. The Career Aspirations Scale (Gray & O’Brien, 2007) and the Career Adaptability Scale (Savickas & Porfeli, 2012) were used with the authors’ permission. Also, the four-factor Occupational Commitment Scale, Occupational Choice Satisfaction Scale, and a questionnaire for demographic data were designed for the study. The psychometric properties of the instruments were sufficient. The results have revealed that occupational commitment and its correlates differ among student samples from vocational technical schools, colleges, and universities, but the affective commitment is higher than the other forms of commitment. Occupational choice satisfaction and satisfaction with studies are positively related with affective, normative, and accumulated occupational commitment. Affective commitment is positively related with career adaptability. Career aspirations and occupational commitment are related with students’ future intentions. According to our results, students with a higher level of career adaptability and a greater occupational choice satisfaction have higher career aspirations. Students’ higher limited alternatives commitment is related to lower career adaptability scores and lower career aspirations.